Adherence and eating experiences differ between participants following a flexitarian diet including red meat or a vegetarian diet including plant-based meat alternatives: findings from a 10-week randomised dietary intervention trial - Gillies, Nicola A.; Worthington, Anna; Li, Larissa; Conner, Tamlin S.; Bermingham, Emma N.; Knowles, Scott O.; Cameron-Smith, David; Hannaford, Rina; Braakhuis, Andrea (Frontiers in Nutrition, 2023)
Background: Flexitarian, vegetarian and exclusively plant-based diets are increasingly popular, particularly amongst young adults. This is the first randomised dietary intervention to investigate the health, wellbeing, and behavioural implications of consuming a basal vegetarian diet that additionally includes low-to-moderate amounts of red meat (flexitarian) compared to one containing plant-based meat alternatives (PBMAs, vegetarian) in young adults (ClinicalTrials.gov NCT04869163). The objective for this analysis is to measure adherence to the intervention, nutrition behaviours, and participants’ eating experiences. Methods: Eighty healthy young adults participated in this 10-week intervention as household pairs. Household pairs were randomised to receive either approximately three serves of red meat (average 390g cooked weight per individual, flexitarian group) or PBMAs (average 350-400g, vegetarian group) per week on top of a basal vegetarian diet. Participants were supported to adopt healthy eating behaviours, and this intervention was developed and implemented using a behaviour change framework. Adherence (eating allocated red meat or PBMA, abstaining from animal-based foods not provided by researchers) was continuously monitored, with total scores calculated at the end of the 10-week intervention. Eating experiences were measured by the Positive Eating Scale and a purpose-designed exit survey, and a food frequency questionnaire measured dietary intake. Analyses used mixed effects modeling taking household clustering into account. Results: The total average adherence score was 91.5 (SD=9.0) out of a possible 100, with participants in the flexitarian group scoring higher (96.1, SD=4.6, compared to 86.7, SD=10.0;p<0.001). Those receiving red meat were generally more satisfied compared to those receiving the PBMAs, even though a leading motivation for participants joining the study was an opportunity to try plant-based eating (35% expressed that this was their interest in taking). Participants in both intervention groups had increased vegetable intake (p<0.001), and reported more positive eating experiences (p=0.020) and satisfaction with eating (p=0.021) at the end of the 10-week intervention relative to baseline. Conclusion: Methods to encourage engagement with the trial were successful, as participants demonstrated excellent adherence to the intervention. Observed differences in participants’ adherence and experiences between flexitarian and vegetarian groups holds implications for the adoption of healthy, sustainable dietary patterns beyond this study alone.